O romance vitral de Adélia Prado - Macedo, Adriane Roberta Ribeiro de (2005)
The present dissertation has as objective to reflect on the process of construction of the narrative speech of Cacos para um vitral, workmanship of Adélia Prado, published in 1980. thus, we elaborate the following question: Knowing that the organization give to the composition to the romance Cacos para um vitral deives a digialogical construction, equivalent and multi-meaming, where is discursive dimension modality retakes the similar literal logic to the composition of stain glass window? Ahead of the object and the problematic one considered, we raise two hypotheses, first, the architextura of the composition of the stain glass window, second, the metalinguistic method cooperates with the assembly of double metaphor: stain glass window text. The research discloses, among other conclusions, that the organization of the text is brock up in direction, approaching the process of construction of the text and the composition of stain glass window